ANALISIS USAHA PENANGKAPAN RAWAI DAN PENGEMBANGANNYA DI KOTA DUMAI - Syofyan, Irwandy; Sari, T. Ersti Yulika; ', Suliani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
Fisheries production in Kota Dumai began to decline over time, and the prohibition on sondong provide opportunities for Longline as alternative fishing gear. The research was conducted on January 25 to February 5, 2016 at Pelabuhan Perikanan Kota Dumai with the aim of the research is to know feasibility of longline business as alternative fishing gear by using survey methods. Longline business as a feasible alternative fishing gear in terms of availability of raw materials, labor availability, market opportunities and business interests with an average value of 3. Financially feasible to be developed at an investment cost incurred on average Rp 16.730.752. BCR value of 2.16 to the value of FRR is 83.1% higher than the bank rate of 7.25% applies. PPC value (payback period of capital) is 1.73 year. In its development longline can be used as the primary fishing gear and alternative. after a review of the feasibility aspects of business development and financial analysis.Keywords : Mini longline, Feasibility, Financial Analysis, Development Direction, PPI Dumai.